The international WAO/EAACI guideline for the management of hereditary angioedema—The 2021 revision and update. Issue 7 (3rd February 2022) - Maurer, Marcus; Magerl, Markus; Betschel, Stephen; Aberer, Werner; Ansotegui, Ignacio J.; Aygören‐Pürsün, Emel; Banerji, Aleena; Bara, Noémi‐Anna; Boccon‐Gibod, Isabelle; Bork, Konrad; Bouillet, Laurence; Boysen, Henrik Balle; et al.
Abstract: Hereditary angioedema (HAE) is a rare and disabling disease for which early diagnosis and effective therapy are critical. This revision and update of the global WAO/EAACI guideline on the diagnosis and management of HAE provides up‐to‐date guidance for the management of HAE. For this update and revision of the guideline, an international panel of experts reviewed the existing evidence, developed 28 recommendations, and established consensus by an online DELPHI process. The goal of these recommendations and guideline is to help physicians and their patients in making rational decisions in the management of HAE with deficient C1 inhibitor (type 1) and HAE with dysfunctional C1 inhibitor (type 2), by providing guidance on common and important clinical issues, such as: (1) How should HAE be diagnosed? (2) When should HAE patients receive prophylactic on top of on‐demand treatment and what treatments should be used? (3) What are the goals of treatment? (4) Should HAE management be different for special HAE patient groups such as children or pregnant/breast‐feeding women? and (5) How should HAE patients monitor their disease activity, impact, and control? It is also the intention of this guideline to help establish global standards for the management of HAE and to encourage and facilitate the use of recommended diagnostics and therapies for all patients. Abstract :